A population‐based study of chronic myeloid leukemia patients treated with imatinib in first line. Issue 1 (18th November 2016) - Castagnetti, Fausto; Di Raimondo, Francesco; De Vivo, Antonio; Spitaleri, Antonio; Gugliotta, Gabriele; Fabbiano, Francesco; Capodanno, Isabella; Mannina, Donato; Salvucci, Marzia; Antolino, Agostino; Marasca, Roberto; Musso, Maurizio; et al.
Abstract : Chronic myeloid leukemia (CML) treatment is based on company‐sponsored and academic trials testing different tyrosine kinase inhibitors (TKIs) as first‐line therapy. These studies included patients selected according to many inclusion–exclusion criteria, particularly age and comorbidities, with specific treatment obligations. In daily clinical practice (real‐life), inclusion–exclusion criteria do not exist, and the treatment outcome does not only depend on the choice of first‐line TKI but also on second‐ and third‐line TKIs. To investigate in a real‐life setting the response and the outcome on first‐line imatinib, with switch to second generation TKIs in case of unsatisfying response or intolerance, we analyzed all newly diagnosed patients ( N = 236), living in two Italian regions, registered in a prospective study according to population‐based criteria and treated front‐line with imatinib. A switch from imatinib to second‐generation TKIs was reported in 14% of patients for side effects and in 24% for failure or suboptimal response, with an improvement of molecular response in 57% of them. The 5‐year overall survival (OS) and leukemia‐related survival (LRS) were 85% and 93%, respectively; the 4‐year rates of MR 3.0 and MR 4.0 were 75% and 48%, respectively. Cardiovascular complications were reported in 4% of patients treated with imatinib alone and in 6% of patients receiving nilotinib as second‐line. Older age (≥70 years) affected OS, but not LRS. These data provide an unbiased reference on the CML management and on the results of TKI treatment in real‐life, according to ELN recommendations, using imatinib as first‐line treatment and second‐generation TKIs as second‐line therapy. Am. J. Hematol. 92:82–87, 2017. © 2016 Wiley Periodicals, Inc.